2022
DOI: 10.1186/s12877-022-02961-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a staged integral art-based cognitive intervention (SIACI) program in older adults with cognitive impairments: protocol for a randomized controlled trial

Abstract: Background Given the aging population worldwide and the COVID-19 pandemic, which has been found to be associated with a deterioration in Alzheimer’s disease (AD) symptoms, investigating methods to prevent or delay cognitive decline in preclinical AD and AD itself is important. The trial described in this protocol aims to evaluate the effects of a staged integral art-based cognitive intervention (SIACI) in older adults with CIs (preclinical AD [SCD or MCI] and mild AD), in order to gather eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…There are 11 EEG studies and 10 ERP studies. Studies have used EEG methods (Cai et al, 2022; Kwon et al, 2013; Mukherjee et al, 2013; Okubo, 2011; Sun et al, 2020; Yang et al, 2012; Yang et al, 2016) or ERP (Cao et al, 2017; Välimäki et al, 2021; Yan et al, 2022; Zhao et al, 2021) to identify some changes in the neural function of patients in response to the intervention. Studies also used EEG (Fitriana et al, 2021; Grusendorf, 1994; Jin et al, 2022) or ERP (Bi et al, 2022; Cao et al, 2015; Cao, Si, Li, & Guo, 2022; Cao, Si, Li, Guo, & Yue, 2022; Dai et al, 2016; Peters et al, 2014) to explore the difference in brain activity between different severity patients or compared with normal subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are 11 EEG studies and 10 ERP studies. Studies have used EEG methods (Cai et al, 2022; Kwon et al, 2013; Mukherjee et al, 2013; Okubo, 2011; Sun et al, 2020; Yang et al, 2012; Yang et al, 2016) or ERP (Cao et al, 2017; Välimäki et al, 2021; Yan et al, 2022; Zhao et al, 2021) to identify some changes in the neural function of patients in response to the intervention. Studies also used EEG (Fitriana et al, 2021; Grusendorf, 1994; Jin et al, 2022) or ERP (Bi et al, 2022; Cao et al, 2015; Cao, Si, Li, & Guo, 2022; Cao, Si, Li, Guo, & Yue, 2022; Dai et al, 2016; Peters et al, 2014) to explore the difference in brain activity between different severity patients or compared with normal subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies recorded EEG during intervention or recorded the EEG of participants with eyes open and closed before and after intervention (Severtsen & Bruya, 1986; Wong et al, 2018). Other studies recorded ERP when subjects were performing specific tasks after intervention or in some specific circumstances, that is, using an experimental paradigm, such as the odd ball paradigm (Cui et al, 2021; Peters et al, 2014; Yan et al, 2022; Yasukouchi et al, 1995; Zhao et al, 2021), Stroop task (Cao, Si, Li, & Guo, 2022; Lees et al, 2016; Lees et al, 2020; Lees & Lal, 2017), and passively viewing pictures (Bi et al, 2022; Cao et al, 2017). Forty‐four studies reported the sample size, ranging from one to 414, with an average of 55 and a median of 36.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After publication of this article [ 1 ], the authors reported that the details for affiliation 1 were incorrectly given as ‘Research Center for Nursing Theory and Practice, Fujian Provincial Hospital, No. 134 Dongjie Street, Gulou District, Fuzhou 350001, Fujian Province, China’ but should have been ‘Research Center for Nursing Theory and Practice, Fujian Provincial Hospital, Shengli Clinical Medical College of Fujian Medical University, No.…”
mentioning
confidence: 99%